THE RELATIONSHIP BETWEEN WORK POSTURE AND COMPLAINTS OF LOW BACK PAIN AT PT. PRIMA CAHAYA UTAMA IN 2024 - Khotimah; Sufyan Anwar; Onetusfifsi Putra; Kiswanto; Siti Maisyaroh Fitri Siregar (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Complaints Low Back Pain generally occur in workers due to work postures that are not ergonomic. Work posture is the position of a worker in carrying out an activity, one important aspect that influences the analysis of work effectiveness is how workers position their bodies.. This study aim to see if there was a relationship between work postures applied by workers and complaints of low back pain experienced by workers. This research method was a quantitative with a cross-sectional design approach, which was used to see the relationship between the independent variables (age, gender, work mass, education level and work posture) and the dependent variable (complaints of low back pain). The sample was taken by total sampling, involving 55 workers at PT Prima Cahaya Utama. Data analysis included univariate, and bivariate analysis, using the chi-square test. The results of the analysis showed that age (p-value 0.789), gender (p-value 1.000), working mass (p-value 1.000), education level (p-value 0.775) had no significant relationship with low back pain complaints. However, work posture (p-value 0.001) showed a significant relationship with complaints of low back pain. There is a relationship between work posture and complaints of low back pain, therefore companies need to pay attention to employee posture at work.